Evolution of organically bound metals during coal combustion in air and O2/CO2 mixtures: A case study of Victorian brown coal - Zhang, L.; Jiao, F.; Binner, E.; Chen, L.; Bhattacharya, S.; Ninomiya, Y.; Li, Chun-Zhu (Elsevier, 2011)
This study aims to clarify the transformation behaviour of organically bound metals during coal combustion in a variety of bulk gases, i.e. air versus O2/CO2. A Victorian brown coal containing few mineral grains was tested. Coal combustion was conducted in a lab-scale drop-tube furnace (DTF) at 1073 K and 1273 K in air and two O2/CO2 mixtures (21/79 and 27/73, v/v). The results indicate that, coal pyrolysis is the primary step determining the vaporisation/loss extents of the organically bound elements, irrespective of bulk gas composition (N2 versus CO2). Noticeable difference for the subsequent transformation of metallic vapours was however observed during char combustion in different bulk gases and at different furnace temperatures. Vaporisation of the char-bound inorganic species continued steadily with char oxidation proceeding at 1073 K. In contrast, at 1273 K, a large proportion of the pyrolysis-driven inorganic vapours interacted with the char-bound metals to further convert into solid species during char oxidation. A descending sequence of air ≥27% O2/73% CO2 >21% O2/79% CO2 was observed for the overall ash loss after the completion of coal combustion, which is in consistence with the trend for burning coal particle temperature in these gases. Though the variation in mass loss of most the elements was insignificant among difference bulk gases, a larger fraction of gaseous S and Na was found remaining in solid ash particles with bulk gas shifting from air to either O2/CO2 mixture, due to the favourable formation of Na2SO4 and Na alumino-silicate under oxy-firing conditions. Formation of the former species was favoured by conversion of NaCl into Na2SO4 under the assistance of CO2 and steam. Formation of Na alumino-silicate was on the other hand promoted by the intimate contact between volatiles and char surface. These two Na-bearing species has the potential to melt and coagulate into large agglomerates at the furnace temperature of 1273 K, thereby potentially triggering extra fouling and slagging problems during oxy-fuel combustion.